Comparative Evaluation Between Modified Bleach Method and Conventional Z-N Staining Method in Improved Detection of Acid–Fast Bacilli in Tubercular Lymphadenitis - Hossain, Md Shajjad; Habib, Saiqua; Chakravarty, Saumitra; Nahid, Md Shahrior; Sultana, Mohosina (Bangladesh Journal of Medical Microbiology, 2025)
Background: This cross-sectional study was carried out first in Bangladesh to compare a newer ‘modified bleach method’ and traditional Z-N staining method for improved structural and morphological detection of Acid-Fast Bacilli (AFB) in Tubarcular lymphadenitis. Objectives: This study was aimed to compare the effectiveness of modified bleach concentration method with the conventional Z-N method to detect Acid fast bacilli (AFB) for the diagnosis of Tuberculosis in lymph node cytology. Methodology: This was a cross-sectional study conducted from January 2019 to January 2022 in the Department of Pathology at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. This study executed both conventional Z-N method and modified bleach concentration method in each sample for total 98 tubercular lymphadenitis cases. Then the data were compared with each other and with GeneXpert which was the reference control for this study. Results: This study revealed that the Bleach method detected more positive AFB than the Z-N method. Among the 98 cases, a total 63 cases were AFB positive (64.29%) and 35 cases (35.71%) were AFB negative by bleach concentration method. On the other hand, 51 (52.04%) cases were AFB positive, and 47 cases (47.96%) were AFB negative by Z-N staining method. Not only that but among the 47 negative cases of the conventional Z-N method, 13 cases were found to be positive in modified Bleach method. Conclusion: In conclusion, the application of the bleach method clearly improves microscopic detection and can be a useful adjunct to routine cytology. Bangladesh Journal of Medical Microbiology, July 2024;18(2):86-92